2015
DOI: 10.17577/ijertv4is040808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Replacement of Natural Sand With Gold Mine Tailings on Some Properties of Masonry Mortars

Abstract: Sand constitutes bulk of cement mortar. Meeting the demand for sand in the construction industry without exploiting the natural resources is becoming a challenging task. In search of an alternative material for natural sand, gold mine tailings are substituted partially for natural sand in the production of masonry mortars. Natural sand is reconstituted by replacing it with 10%, 20% and 30% gold mine tailings. The effect of replacement on the properties of masonry mortars such as water retentivity, drying shrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The study allowed to see the evolution of the concrete compressive strength of the substitution of NRS by GMT from 0 up to 100% of the experimental domain defined above. The compressive strength was found to vary between 11 and 37 N/mm 2 with 11 N/mm 2 for the total substitution of NRS by GMT with a dosage of 20 kg of GMT (0 kg of NRS), 10 kg of cement, and 40 kg of gravel and 37 N/mm 2 for the dosage of 20 kg of NRS (0 kg of GMT), 15 It was also found that larger quantity of gravel (40 kg) improved the concrete compressive strength from 70% up to 100% of GMT as substitute to NRS when 15 kg of cement was used.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…The study allowed to see the evolution of the concrete compressive strength of the substitution of NRS by GMT from 0 up to 100% of the experimental domain defined above. The compressive strength was found to vary between 11 and 37 N/mm 2 with 11 N/mm 2 for the total substitution of NRS by GMT with a dosage of 20 kg of GMT (0 kg of NRS), 10 kg of cement, and 40 kg of gravel and 37 N/mm 2 for the dosage of 20 kg of NRS (0 kg of GMT), 15 It was also found that larger quantity of gravel (40 kg) improved the concrete compressive strength from 70% up to 100% of GMT as substitute to NRS when 15 kg of cement was used.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…When the amount of GMT is continuously added to the concrete, the compressive strength decreases. There are several possible reasons, including the GMT grain size, its chemical characteristics, and the water/cement ratio [11,[13][14][15][16]]. The fine grading promotes higher water use.…”
Section: Analysis Of the Individual Contribution Of Each Concrete Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…Vignesh, Reddy and Nachiar [8] reported that, in search of an alternative material for natural sand, Witwatersrand gold mine tailings are substituted partially for natural sand in the production of masonry mortars. In order to study the effect of replacing natural sand by gold mine tailings, natural sand was replaced with gold mine tailings at three percentages (10%, 20% and 30%).…”
Section: Introductionmentioning
confidence: 99%